Composition and method for rapid fluidization and solidification of silt sand

By using compositions of surfactant, curing agent and desulfurization tower bottom ash, the silt soil is rapidly fluidized and cured quickly, solving the problems of slow construction speed and low quality of small parts of the space Shaanxi area, and realizing construction Significant improvement in speed and quality.

CN117069461BActive Publication Date: 2025-02-21NANJING HYDRAULIC RES INST +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311078497.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2025-02-21
Estimated Expiration
2043-08-25

AI Technical Summary

Technical Problem

In the prior art, the construction speed of earth backfilling in small parts of the space Shaanxi area is slow, difficult to operate, and low quality assurance rate, which poses great safety and quality hazards.

Method used

Using a composition including surfactant, curing agent and desulfurization tower bottom ash, the silt soil is rapidly fluidized and cured through specific proportions and process steps, thereby improving the construction speed and quality.

Benefits of technology

The construction speed and quality of foundation pits in small parts of the space Shaanxi have been significantly improved, and the problems of slow construction speed, difficulty in operation and low project quality assurance rate have been solved, and construction safety and quality have been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117069461B_ABST
    Figure CN117069461B_ABST
Patent Text Reader

Abstract

The present invention discloses a composition and method for rapidly fluidizing and solidifying silt sand, wherein the composition comprises, by mass, 3 to 6 parts of a surfactant, 5 to 10 parts of a curing agent, and 5 to 10 parts of desulfurization tower bottom ash. The method mainly comprises the following steps: preparing raw materials according to a predetermined ratio; uniformly mixing water and a surfactant to obtain a mixed liquid; putting silt sand into a mixer, adding the mixed liquid and sand after stirring, and stirring again to obtain a slurry-like fluidized silt sand; putting a curing agent into a mixer, and stirring again to obtain a slurry that is fluidized and can be quickly solidified. The present application solves the engineering problems of slow construction speed, difficult operation, and low engineering quality assurance rate in backfilling of small parts of space, and achieves a significant improvement in the construction speed and quality of backfilling of foundation pits in small parts of space.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to earthwork construction technology, in particular to a composition and method for rapidly fluidizing and solidifying silt soil. Background Art

[0002] At present, the quality of earth excavation and backfilling directly affects the construction quality of the entire project. Since the quality defects of earth backfilling are not easy to be found, it is a hidden project, and quality accidents caused by it are also common. Therefore, the quality of earth backfilling should be paid attention to.

[0003] Traditional earthwork backfilling generally adopts manual compaction or mechanical compaction methods based on comprehensive considerations of factors such as construction site conditions, construction machinery, and construction technical requirements. Mechanical compaction methods are divided into strong compaction and rolling methods. Mechanical compaction is mainly aimed at large-scale work site construction. For some projects, such as the replacement of the intermediate dividing strip, the fertilizer trough of the foundation pit, and other small-area earthwork backfilling work in small spaces, manual compaction methods are often used. Manual compaction construction speed is slow, and the backfill compaction degree is difficult to meet the requirements. Therefore, the construction quality cannot be fully guaranteed, and there are major safety and quality risks.

[0004] Therefore, a new technology is needed to solve the above problems. Summary of the invention

[0005] Purpose of the invention: To provide a composition capable of rapidly fluidizing and solidifying silt sand, and a method for fluidizing and rapidly solidifying silt sand based on the composition.

[0006] Technical solution: According to one aspect of the present application, a composition is provided that can rapidly fluidize and solidify silt sand, which comprises, by weight: 3 to 6 parts of a surfactant, 5 to 10 parts of a curing agent, and 5 to 10 parts of desulfurization tower bottom ash; the amount of the composition is 10 to 25 wt%.

[0007] The specific surface area of ​​the curing agent is ≥500m 2 More preferably, the specific surface area is ≥600m 2 / kg or more, more preferably, the specific surface area is ≥650m 2 / kg; further preferably, the specific surface area is ≥700m 2 / kg or more.

[0008] According to one aspect of the present application, the surfactant comprises the following components in parts by weight:

[0009] 10-20 parts of acetone, 20-25 parts of sodium sulfite, 8-12 parts of sodium bisulfite, 5-10 parts of sodium pyrosulfite, 5-10 parts of water, 20-30 parts of 37% industrial formaldehyde, 10-15 parts of sodium lignin sulfonate, and sodium hydroxide capable of adjusting the composition to a predetermined pH.

[0010] According to one aspect of the present application, the curing agent includes the following components in parts by mass: 30-40 parts of mineral powder, 25-35 parts of fly ash, 10-20 parts of steel slag, 10-15 parts of calcium oxide, and 10-15 parts of sodium sulfate.

[0011] According to one aspect of the present application, the surfactant includes the following components in parts by mass: 10-15 parts of acetone, 22-25 parts of sodium sulfite, 10-12 parts of sodium bisulfite, 5-7 parts of sodium pyrosulfite, 5-8 parts of water, 23-28 parts of 37% industrial formaldehyde, 12-14 parts of sodium lignin sulfonate, and sodium hydroxide that can adjust the composition to a predetermined pH.

[0012] According to one aspect of the present application, the surfactant is prepared by the following method:

[0013] Add sodium sulfite, sodium bisulfite, sodium metabisulfite, acetone and water into the reaction kettle, raise the temperature to 50℃~65℃ in 15~45min, and keep the temperature constant for 0.5~1.5h;

[0014] Cool down to below 60℃, add sodium lignin sulfonate and remaining formaldehyde into the reactor, continue to react for 1-2h, adjust the pH value of the solution to 10-12 with sodium hydroxide, raise the temperature to 80-95℃, continue to react for 2-3h, and complete the reaction;

[0015] After the reaction is completed, the mixture is allowed to stand and cool to room temperature to obtain a surfactant suitable for silt sand.

[0016] According to one aspect of the present application, the sum of the three materials of mineral powder, fly ash and steel slag in the curing agent must account for less than 80% of the total mass of the curing agent, and the surface area of ​​the mixture of mineral powder, fly ash and steel slag is ground to 700m 2 / kg or more.

[0017] According to one aspect of the present application, calcium oxide and sodium sulfate account for more than 20% of the total mass of the mixture.

[0018] According to another aspect of the present application, a method for fluidizing and rapidly solidifying silt sand is implemented using the composition described in any of the above technical solutions, and comprises the following steps:

[0019] Step S1, prepare raw materials according to a predetermined ratio, wherein the raw materials include the following components in parts by weight: 30-40 parts of water, 40-50 parts of silt, 5-10 parts of sand, 3-6 parts of surfactant, 5-10 parts of curing agent, and 5-10 parts of new desulfurization tower bottom ash;

[0020] Step S2, uniformly mixing the above-mentioned water and surfactant in parts by mass to obtain a mixed solution;

[0021] Step S3, putting the above-mentioned silt sand by mass into a mixer, stirring for 15 to 45 seconds, adding the mixed solution, sand, and newly produced desulfurization tower bottom ash in step 2 into the mixer, and stirring for another 2 to 3 minutes to obtain a slurry-like fluidized silt sand;

[0022] Step S4: Add the curing agent in the above mass fraction into a mixer and stir for 2 to 3 minutes to obtain a fluid and curable silt sand slurry.

[0023] According to one aspect of the present application, 30-35 parts of water, 40-45 parts of soil, 5-7 parts of sand, 3-5 parts of surfactant, 6 parts of curing agent, and 8 parts of new desulfurization tower bottom ash.

[0024] According to one aspect of the present application, the amount of the surfactant is 3-6%, and the amount of the curing agent is 5-10%.

[0025] According to one aspect of the present application, the amount of sand used is 3-6%, and the particle size is 1.25 mm to 5.0 mm, which is machine-made sand or river sand.

[0026] The mechanism of action of sand is to provide hard materials in the process of mixing silt and sand, which can form shear bodies, increase the dispersibility and fluidity between silt and sand, and at the same time, improve the solidification strength of fluidized soil in the later stage. If the particle size is too small, the fluidity of the system will deteriorate, so sand of 1.25-5.0mm is selected to ensure that the fluidity and strength of the system meet the requirements. That is, hard materials are provided in the process of mixing silt and sand, which can form shear bodies, increase the dispersibility and fluidity between silt and sand, and at the same time, improve the solidification strength of fluidized soil in the later stage. According to one aspect of the present application, the mixer is a disc vertical shaft mixer, and the power is not less than 30kW, and the rotation speed is 60r / min~90 r / min.

[0027] Newly produced desulfurization tower bottom ash is a by-product in the factory flue. It contains a large amount of alkali and sulfate. After mixing with silt soil, it increases the early strength and has a certain effect on the activation of the curing agent. The curing agent is increased by grinding and activated by alkaline stimulation, increasing the solidification and hardening strength of the fluidized soil. The fluidized soil must be mixed evenly with a powerful disc vertical shaft mixer to make it fluidized.

[0028] Beneficial effect: It solves the engineering problems of slow construction speed, difficult operation and low engineering quality assurance rate in backfilling of small space parts, and significantly improves the construction speed and quality of backfilling of foundation pits in small space parts. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a schematic diagram of the compression test block of the present invention.

[0030] Figure 2 It is a schematic diagram of fluidized soil pumping of the present invention.

[0031] Figure 3 It is a schematic diagram of fluidized soil mixing of the present invention.

[0032] Figure 4 It is a schematic diagram of the relationship among fluidity, curing time and curing strength of Example 1 of the present invention.

[0033] Figure 5 It is a schematic diagram of the change trend of yield stress and plastic viscosity with the surfactant dosage of the present invention. DETAILED DESCRIPTION

[0034] In this application, the specific proportions are 30-40 parts of water, 40-50 parts of silt, 5-10 parts of sand, 3-6 parts of surfactant, 5-10 parts of curing agent, and 5-10 parts of desulfurization tower bottom ash, calculated by mass. In this application, desulfurization tower bottom ash refers to newly produced desulfurization tower bottom ash, the same below.

[0035] Preferably, the ratio can be: 30-35 parts of water, 40-45 parts of soil, 5-7 parts of sand, 3-5 parts of surfactant, 6 parts of curing agent, and 8 parts of new desulfurization tower bottom ash.

[0036] In one embodiment, the sand is machine-made sand or river sand, and the particle size is 1.25 mm to 5.0 mm.

[0037] In one embodiment, the surfactant includes the following components and the mass parts of each component are: 10-20 parts of acetone, 20-25 parts of sodium sulfite, 8-12 parts of sodium bisulfite, 5-10 parts of sodium pyrosulfite, 5-10 parts of water, 20-30 parts of 37% industrial formaldehyde, 10-15 parts of sodium lignin sulfonate, and 5-10 parts of sodium hydroxide.

[0038] In one embodiment, preferably, the surfactant includes the following materials in parts by mass: 10-15 parts of acetone, 22-25 parts of sodium sulfite, 10-12 parts of sodium bisulfite, 5-7 parts of sodium pyrosulfite, 5-8 parts of water, 23-28 parts of 37% industrial formaldehyde, 12-14 parts of sodium lignin sulfonate, and an appropriate amount of sodium hydroxide (the amount used to adjust the pH to a predetermined range).

[0039] In one embodiment, the curing agent is composed of five parts: mineral powder, fly ash, steel slag, calcium oxide, and sodium sulfate. The weight of each component is as follows: 30-40 parts of mineral powder, 25-35 parts of fly ash, 10-20 parts of steel slag, 10-15 parts of calcium oxide, and 10-15 parts of sodium sulfate. The sum of the three materials of mineral powder, fly ash, and steel slag in the curing agent must account for less than 80% of the total amount of the curing agent, and the mixture of mineral powder, fly ash, and steel slag must be ground to 700m 2 / kg or more. Calcium oxide and sodium sulfate account for more than 20% of the mixture.

[0040] In one embodiment, the preparation method of the surfactant is as follows:

[0041] 1) Install agitator, thermometer, ventilation pipe and reactor;

[0042] 2) Add sodium sulfite, sodium bisulfite, sodium metabisulfite, acetone and water into the reaction kettle, raise the temperature to 50°C~65°C in about 30 minutes, and keep the temperature constant for 0.5~1.5 hours;

[0043] 3) Add part of the formaldehyde solution dropwise during constant temperature and stirring, the addition time is about 0.5 to 2.5 hours, the temperature is raised to 70°C to 95°C, and the temperature is kept constant for 3 to 6 hours;

[0044] 4) Cool down to below 60°C, add sodium lignin sulfonate and remaining formaldehyde into the reactor, continue to react for 1-2 hours, adjust the pH value of the solution to 10-12 with sodium hydroxide, heat to 80-95°C, continue to react for 2-3 hours, and complete the reaction;

[0045] 5) After the reaction is completed, the mixture is allowed to stand and cool to 20°C to obtain a surfactant suitable for silt sand.

[0046] In one embodiment, using the above-mentioned materials, a construction method for fluidizing silt sand includes the following steps:

[0047] Step 1: Add silt sand into the mixer; if the silt sand block is too large to be put into the mixer, the silt sand block should be broken into small blocks according to the size of the mixer feed port;

[0048] Step 2, uniformly mixing water and a surfactant in predetermined mass fractions to obtain a mixed solution;

[0049] Step 3: Stir the silt sand for 30 seconds, add the mixed liquid, sand and newly produced desulfurization tower bottom ash in step 2 into the mixer, and stir for 2 to 3 minutes to obtain a slurry-like fluid silt sand.

[0050] Step 4: Add a predetermined amount of curing agent by mass into a mixer and stir for 2 to 3 minutes to obtain a fluid and curable silt sand slurry.

[0051] In some embodiments, other sequences may be used. Steps one and two are merely for the convenience of description and do not limit the sequence, such as the chronological sequence.

[0052] The alkali content of the newly produced desulfurization tower bottom ash is higher, which can increase the strength of the system. After being placed for a period of time, the pH value of the desulfurization tower bottom ash decreases, and its contribution to the strength of the system becomes smaller.

[0053] In a further embodiment, the construction site mixer is a disc vertical shaft mixer with a power of not less than 30 kW and a rotation speed of 60 r / min to 90 r / min.

[0054] Example 1: In an engineering case, the specific implementation process is as follows:

[0055] Preparation of surfactant: Weigh various raw materials for preparing surfactant as required, the mass parts of each component are: 15 parts of acetone, 22 parts of sodium sulfite, 10 parts of sodium bisulfite, 8 parts of sodium pyrosulfite, 8 parts of water, 20 parts of 37% industrial formaldehyde, 10 parts of sodium lignin sulfonate, and 7 parts of sodium hydroxide. The preparation method of surfactant is as follows:

[0056] 1) Install agitator, thermometer, ventilation pipe and reactor;

[0057] 2) Add sodium sulfite, sodium bisulfite, sodium metabisulfite, acetone and water into the reactor, slowly heat for about 30 minutes, raise the temperature to 60°C, and keep the temperature constant for 1.0 hour;

[0058] 3) Add 60% of the designed amount of formaldehyde solution dropwise during constant temperature and stirring for about 2.0 hours, raise the temperature to 80°C, and keep the temperature constant for 4 hours;

[0059] 4) Cool down to 55°C, add sodium lignin sulfonate and the remaining 40% formaldehyde into the reactor, continue to react for 2 hours, adjust the pH value of the solution to 10 with sodium hydroxide, heat to 90°C, and continue to react for 3 hours to complete the reaction;

[0060] 5) After the reaction is completed, the mixture is allowed to stand and cool to 20°C to obtain a surfactant suitable for silt sand.

[0061] Preparation of curing agent: weigh the raw materials of mineral powder, fly ash, steel slag, calcium oxide and sodium sulfate for preparing the curing agent as required, including 35 parts of mineral powder, 25 parts of fly ash and 10 parts of steel slag; put the weighed mineral powder, fly ash and steel slag into the grinding machine at the same time and grind them to a specific surface area of ​​≥700m 2 / kg or more.

[0062] Weigh 15 parts of calcium oxide and 15 parts of sodium sulfate, and mix them evenly with the ground mineral powder, fly ash, and steel slag mixed powder.

[0063] Preparation of fluidized silt sand: weigh a certain amount of water, silt sand, sand, surfactant, curing agent, and new desulfurization tower bottom ash as required. The mass fractions of each component are: 36 parts of water, 45 parts of silt sand, 5 parts of sand, 4 parts of surfactant, 6 parts of curing agent, and 5 parts of new desulfurization tower bottom ash.

[0064] The on-site mixer is a disc vertical shaft mixer with a capacity of 2.5m 3 , the mixer power is 35kW and the blade speed is 60r / min.

[0065] The construction method of fluidizing silt soil includes the following steps:

[0066] Step 1: Clean the large stone impurities in the silt soil and put the silt soil into the mixer;

[0067] Step 2, uniformly mixing water and a surfactant in predetermined mass fractions to obtain a mixed solution;

[0068] Step 3: Start the mixer and stir the silt for 30 seconds. Add the mixed solution in step 2 into the mixer, then add river sand and desulfurization tower bottom ash, and stir for another 3 minutes to obtain a slurry-like fluid silt.

[0069] Step 4: Add a predetermined amount of curing agent by mass into a mixer and stir for 3 minutes to obtain a fluid and curable silt sand slurry.

[0070] When the silt sand blocks are too large to be put into the mixer, they should be broken into small blocks according to the size of the mixer feed port.

[0071] Fluid silt performance test data:

[0072] Fluidization indexes of fluidized silt sand: yield stress 27Pa; plastic viscosity 61 mPa.s; fluidity state is slurry and good flow;

[0073] The compressive strength of fluidized silt sand is: 240 kPa at 1d, 620 kPa at 3d and 1800 kPa at 7d.

[0074] Taking the mix ratio of Example 1 as an example, a chart is used to characterize the relationship between fluidity, curing time, and curing strength. The fluidity is represented by fluidity, and the test method of fluidity is shown in the fluidity test method in the manual. Figure 4 shown.

[0075] Example 2: Preparation of surfactant

[0076] Various raw materials for preparing surfactants were weighed as required. The mass parts of each component were: 13 parts of acetone, 21 parts of sodium sulfite, 11 parts of sodium bisulfite, 10 parts of sodium pyrosulfite, 9 parts of water, 20 parts of 37% industrial formaldehyde, 10 parts of sodium lignin sulfonate, and 6 parts of sodium hydroxide.

[0077] The preparation method of the surfactant is as follows:

[0078] 1) Install agitator, thermometer, ventilation pipe and reactor;

[0079] 2) Add sodium sulfite, sodium bisulfite, sodium metabisulfite, acetone and water into the reactor, slowly heat for about 30 minutes, raise the temperature to 50°C, and keep the temperature constant for 1.5 hours;

[0080] 3) Add 60% of the designed amount of formaldehyde solution dropwise during constant temperature and stirring, it takes about 1.5 hours, heat to 80°C, and keep the temperature constant for 4 hours;

[0081] 4) Cool down to 50°C, add sodium lignin sulfonate and the remaining 40% formaldehyde into the reactor, continue the reaction for 2 hours, adjust the pH value of the solution to 9 with sodium hydroxide, heat to 90°C, and continue the reaction for 2.5 hours to complete the reaction;

[0082] 5) After the reaction is completed, the mixture is allowed to stand and cool to 20°C to obtain a surfactant suitable for silt sand.

[0083] Preparation of curing agent: weigh the raw materials for preparing the curing agent, mineral powder, fly ash, steel slag, calcium oxide, and sodium sulfate as required, including 40 parts of mineral powder, 25 parts of fly ash, and 10 parts of steel slag;

[0084] Put the weighed mineral powder, fly ash and steel slag into the grinding machine at the same time and grind them to a specific surface area of ​​730m 2 / kg.

[0085] Weigh 12 parts of calcium oxide and 13 parts of sodium sulfate, and mix them evenly with the ground mineral powder, fly ash, and steel slag mixed powder.

[0086] Preparation of fluidized silt sand: weigh a certain amount of water, silt sand, sand, surfactant, curing agent, and new desulfurization tower bottom ash as required. The mass fractions of each component are: 30 parts of water, 45 parts of silt sand, 7 parts of sand, 5 parts of surfactant, 8 parts of curing agent, and 5 parts of new desulfurization tower bottom ash.

[0087] The on-site mixer is a disc vertical shaft mixer with a capacity of 2.5m 3 , the mixer power is 35kW and the blade speed is 90r / min.

[0088] The construction method of fluidizing silt soil includes the following steps:

[0089] Step 1: Clean the large stone impurities in the silt soil and put the silt soil into the mixer;

[0090] Step 2, uniformly mixing water and a surfactant in predetermined mass fractions to obtain a mixed solution;

[0091] Step 3: Start the mixer and stir the silt for 30 seconds. Add the mixed solution in step 2 into the mixer, then add river sand and desulfurization tower bottom ash, and stir for another 3 minutes to obtain a slurry-like fluid silt.

[0092] Step 4: Add a predetermined amount of curing agent by mass into a mixer and stir for 2 minutes to obtain a fluid and curable silt sand slurry.

[0093] Experimental data on fluid silt sand performance:

[0094] The fluidity indicators of fluidized silt sand are yield stress of 34Pa and plastic viscosity of 79 mPa.s; it is in slurry form and has good fluidity.

[0095] The compressive strength of fluidized silt sand is 470 kPa at 1d, 1280 kPa at 3d, and 2100 kPa at 7d.

[0096] Example 3: Preparation of surfactant

[0097] Various raw materials for preparing surfactants were weighed as required. The mass parts of each component were: 11 parts of acetone, 22 parts of sodium sulfite, 10 parts of sodium bisulfite, 7 parts of sodium pyrosulfite, 8 parts of water, 22 parts of 37% industrial formaldehyde, 12 parts of sodium lignin sulfonate, and 8 parts of sodium hydroxide.

[0098] The preparation method of the surfactant is as follows:

[0099] 1) Install agitator, thermometer, ventilation pipe and reactor;

[0100] 2) Add sodium sulfite, sodium bisulfite, sodium metabisulfite, acetone and water into the reactor, slowly heat for about 30 minutes, raise the temperature to 55°C, and keep the temperature constant for 1.0 hour;

[0101] 3) Add 55% formaldehyde solution in the designed amount dropwise during constant temperature and stirring, it takes about 1.0 hour, heat to 80°C, and keep the temperature constant for 4 hours;

[0102] 4) Cool down to 45°C, add sodium lignin sulfonate and the remaining 45% formaldehyde into the reactor, continue to react for 2 hours, adjust the pH value of the solution to 10 with sodium hydroxide, heat to 90°C, and continue to react for 2.5 hours to complete the reaction;

[0103] 5) After the reaction is completed, the mixture is allowed to stand and cool to 20°C to obtain a surfactant suitable for silt sand.

[0104] Preparation of curing agent: weigh the raw materials for preparing the curing agent, including 30 parts of ore powder, 35 parts of fly ash and 15 parts of steel slag, including 30 parts of ore powder, 35 parts of fly ash and 15 parts of steel slag;

[0105] Put the weighed mineral powder, fly ash and steel slag into the grinding machine at the same time and grind them to a specific surface area of ​​720m 2 / kg.

[0106] Weigh 10 parts of calcium oxide and 10 parts of sodium sulfate, and mix them evenly with the ground mineral powder, fly ash, and steel slag mixed powder.

[0107] Preparation of fluidized silt sand: weigh a certain amount of water, silt sand, sand, surfactant, curing agent, and new desulfurization tower bottom ash as required. The mass fractions of each component are: 40 parts of water, 40 parts of silt sand, 7 parts of sand, 3 parts of surfactant, 5 parts of curing agent, and 5 parts of new desulfurization tower bottom ash.

[0108] The on-site mixer is a disc vertical shaft mixer with a capacity of 2.5m 3 , the mixer power is 35kW and the blade speed is 90r / min.

[0109] The construction method of fluidizing silt soil includes the following steps:

[0110] Step 1: Clean the large stone impurities in the silt soil and put the silt soil into the mixer;

[0111] Step 2, uniformly mixing water and a surfactant in predetermined mass fractions to obtain a mixed solution;

[0112] Step 3: Start the mixer and stir the silt for 30 seconds. Add the mixed solution in step 2 into the mixer, then add river sand and desulfurization tower bottom ash, and stir for another 3 minutes to obtain a slurry-like fluid silt.

[0113] Step 4: Add a predetermined amount of curing agent by mass into a mixer and stir for 2 minutes to obtain a fluid and curable silt sand slurry.

[0114] Experimental data on the performance of fluid silt sand:

[0115] The fluidity indicators of fluidized silt sand are: yield stress is 21Pa, plastic viscosity is 53 mPa.s, slurry-like and has good fluidity.

[0116] The compressive strength of fluidized silt sand is: 190 kPa at 1d, 540 kPa at 3d, and 1080 kPa at 7d.

[0117] Example 4: Preparation of surfactant

[0118] Various raw materials for preparing surfactants were weighed as required. The mass parts of each component were: 14 parts of acetone, 22 parts of sodium sulfite, 10 parts of sodium bisulfite, 7 parts of sodium pyrosulfite, 6 parts of water, 22 parts of 37% industrial formaldehyde, 14 parts of sodium lignin sulfonate, and 5 parts of sodium hydroxide.

[0119] The preparation method of the surfactant is as follows:

[0120] 1) Install agitator, thermometer, ventilation pipe and reactor;

[0121] 2) Add sodium sulfite, sodium bisulfite, sodium metabisulfite, acetone and water into the reactor, slowly heat for about 30 minutes, raise the temperature to 65°C, and keep the temperature constant for 1.0 hour;

[0122] 3) Add 55% of the designed formaldehyde solution dropwise during constant temperature and stirring for about 2.5 hours, raise the temperature to 80°C, and keep the temperature constant for 3 hours;

[0123] 4) Cool down to 45°C, add sodium lignin sulfonate and the remaining 45% formaldehyde into the reactor, continue to react for 2 hours, adjust the pH value of the solution to 10 with sodium hydroxide, heat to 85°C, and continue to react for 2.5 hours to complete the reaction;

[0124] 5) After the reaction is completed, the mixture is allowed to stand and cool to 20°C to obtain a surfactant suitable for silt sand.

[0125] Preparation of curing agent: weigh the raw materials for preparing the curing agent, including 35 parts of ore powder, 30 parts of fly ash and 10 parts of steel slag as required;

[0126] Put the weighed mineral powder, fly ash and steel slag into the grinding machine at the same time and grind them to a specific surface area of ​​720m 2 / kg.

[0127] Weigh 10 parts of calcium oxide and 15 parts of sodium sulfate, and mix them evenly with the ground mineral powder, fly ash, and steel slag mixed powder.

[0128] Preparation of fluidized silt sand: weigh a certain amount of water, silt sand, sand, surfactant, curing agent, and new desulfurization tower bottom ash as required. The mass fractions of each component are: 30 parts of water, 45 parts of silt sand, 5 parts of sand, 6 parts of surfactant, 9 parts of curing agent, and 5 parts of new desulfurization tower bottom ash.

[0129] The on-site mixer is a disc vertical shaft mixer with a capacity of 3.0m 3 , the mixer power is 40kW and the blade speed is 60r / min.

[0130] The construction method of fluidizing silt soil includes the following steps:

[0131] Step 1: Clean the large stone impurities in the silt soil and put the silt soil into the mixer;

[0132] Step 2, uniformly mixing water and a surfactant in predetermined mass fractions to obtain a mixed solution;

[0133] Step 3: Start the mixer and stir the silt for 30 seconds. Add the mixed solution in step 2 into the mixer, then add river sand and desulfurization tower bottom ash, and stir for another 3 minutes to obtain a slurry-like fluid silt.

[0134] Step 4: Add a predetermined amount of curing agent by mass into a mixer and stir for 2 minutes to obtain a fluid and curable silt sand slurry.

[0135] Experimental data on the performance of fluid silt sand:

[0136] Fluidity index: yield stress is 39Pa, plastic viscosity is 87 mPa.s, slurry and good fluidity.

[0137] The compressive strength is: 570 kPa at 1d, 1380 kPa at 3d, and 2300 kPa at 7d.

[0138] Example 5: Preparation of surfactant

[0139] Various raw materials for preparing surfactants were weighed as required. The mass parts of each component were: 15 parts of acetone, 21 parts of sodium sulfite, 10 parts of sodium bisulfite, 8 parts of sodium pyrosulfite, 8 parts of water, 20 parts of 37% industrial formaldehyde, 13 parts of sodium lignin sulfonate, and 5 parts of sodium hydroxide.

[0140] The preparation method of the surfactant is as follows:

[0141] 1) Install agitator, thermometer, ventilation pipe and reactor;

[0142] 2) Add sodium sulfite, sodium bisulfite, sodium metabisulfite, acetone and water into the reactor, slowly heat for about 30 minutes, raise the temperature to 60°C, and keep the temperature constant for 1.0 hour;

[0143] 3) Add 55% of the designed formaldehyde solution dropwise during constant temperature and stirring for about 2.5 hours, raise the temperature to 80°C, and keep the temperature constant for 3 hours;

[0144] 4) Cool down to 55°C, add sodium lignin sulfonate and the remaining 45% formaldehyde into the reactor, continue the reaction for 2 hours, adjust the pH value of the solution to 10 with sodium hydroxide, heat to 80°C, and continue the reaction for 2.5 hours to complete the reaction;

[0145] 5) After the reaction is completed, the mixture is allowed to stand and cool to 20°C to obtain a surfactant suitable for silt sand.

[0146] Preparation of curing agent: weigh the raw materials for preparing the curing agent, including 30 parts of ore powder, 30 parts of fly ash and 16 parts of steel slag, including 30 parts of ore powder, 30 parts of fly ash and 16 parts of steel slag;

[0147] Put the weighed mineral powder, fly ash and steel slag into the grinding machine at the same time and grind them to a specific surface area of ​​720m 2 / kg.

[0148] Weigh 14 parts of calcium oxide and 10 parts of sodium sulfate, and mix them evenly with the ground mineral powder, fly ash, and steel slag mixed powder.

[0149] Preparation of fluidized silt sand: weigh a certain amount of water, silt sand, sand, surfactant, curing agent, and new desulfurization tower bottom ash as required. The mass fractions of each component are: 35 parts of water, 45 parts of silt sand, 5 parts of sand, 3 parts of surfactant, 5 parts of curing agent, and 6 parts of new desulfurization tower bottom ash.

[0150] The on-site mixer is a disc vertical shaft mixer with a capacity of 3.0m 3 ,The mixer power is 40kW and the blade speed is 60r / min.

[0151] The construction method of fluidizing silt soil includes the following steps:

[0152] Step 1: Clean the large stone impurities in the silt soil and put the silt soil into the mixer;

[0153] Step 2, uniformly mixing water and a surfactant in predetermined mass fractions to obtain a mixed solution;

[0154] Step 3: Start the mixer and stir the silt for 30 seconds. Add the mixed solution in step 2 into the mixer, then add river sand and desulfurization tower bottom ash, and stir for another 3 minutes to obtain a slurry-like fluid silt.

[0155] Step 4: Add a predetermined amount of curing agent by mass into a mixer and stir for 2 minutes to obtain a fluid and curable silt sand slurry.

[0156] Experimental data on the performance of fluid silt sand:

[0157] Fluidity indicators are: yield stress 33Pa, plastic viscosity 71 mPa.s; slurry-like and good fluidity;

[0158] The compressive strength is: 320kPa at 1d, 680kPa at 3d, and 1490 kPa at 7d.

[0159] In the above examples, the amount of the composition, i.e., the ratio of the total mass of the composition to the total mass of water, silt and sand, is 14.85%, 18.0%, 13.0%, 20.0% and 14.14%, respectively. Among them, the mass percentages of the surfactant are 3.96%, 5.0%, 3.0%, 6.0% and 3.03%, respectively. The mass percentages of the curing agent are 5.94%, 8.0%, 5.0%, 9.0% and 5.05%, respectively.

[0160] In the above embodiment: the change trend of the fluidity index with the surfactant content. The fluidity index includes yield stress and plastic viscosity, which reflect the fluidity properties of the fluidized silt sand. Generally speaking, the smaller the yield stress and plastic viscosity, the better the fluidity. There is a certain negative correlation between the surfactant content and the fluidity index, that is, the higher the surfactant content, the lower the fluidity index, and the better the fluidity. This is because the surfactant can reduce the surface tension between the silt sand particles, increase its wetting effect on water, and thus reduce the viscosity and internal friction of the fluidized silt sand.

[0161] The compressive strength reflects the solidification effect and bearing capacity of fluid silt sand. Generally speaking, the higher the compressive strength, the better the solidification effect. It is found that there is a certain positive correlation between the curing agent content and the compressive strength, that is, the higher the curing agent content, the higher the compressive strength. This is because the curing agent can promote the hydration reaction between silt sand particles, improve its hardening degree and compressive resistance.

[0162] In addition to being related to the composition and dosage of the surfactant, fluidity is also related to the dosage of the curing agent and the specific surface area. Therefore, in the experiment, it is a multivariate nonlinear relationship. The curing speed is also related to the parameters of multiple components. For this reason, experiments will be conducted on important properties in the following text.

[0163] The test results of this application show that:

[0164] Other parameters remain unchanged, only the water content changes. The more water there is, the lower the yield stress, the lower the plastic viscosity, the higher the fluidity, and the lower the compressive strength.

[0165] The other parameters remain unchanged, only the silt soil changes. The more silt soil there is, the higher the yield stress, the higher the plastic viscosity, the lower the fluidity, and the higher the compressive strength.

[0166] The other parameters remain unchanged, only the surfactant dosage changes. The more surfactant dosage increases, the lower the yield stress, the lower the plastic viscosity, the higher the fluidity, and the compressive strength decreases to a small extent.

[0167] Other parameters remain unchanged, only the curing agent changes. The more curing agent there is, the higher the yield stress, the higher the plastic viscosity, the lower the fluidity, and the higher the compressive strength.

[0168] Other parameters remain unchanged, only the specific surface area of ​​the curing agent changes. The larger the specific surface area, the higher the yield stress, the higher the plastic viscosity, the lower the fluidity, and the higher the compressive strength.

[0169] Other parameters remain unchanged, only the newly produced desulfurization tower bottom ash changes. The thicker the desulfurization tower bottom ash, the higher the yield stress, the plastic viscosity, the lower the fluidity, and the higher the compressive strength.

[0170] Regarding parameters such as yield stress, the following is explained: the yield stress of a fluid refers to the fact that for some non-Newtonian fluids, when the applied shear stress is small, the fluid only deforms but does not flow. When the shear stress increases to a certain value, the fluid begins to flow. The shear stress at this time is called the yield stress of the fluid. Generally, a rheometer is used to test the yield stress. Under laminar flow conditions, the slope value when the shear stress is linearly related to the shear rate. Plastic viscosity reflects the strength of the internal friction between suspended solid particles, between solid particles and liquid phase, and within the continuous liquid phase when the destruction and recovery of the fluid are in dynamic equilibrium under laminar flow conditions.

[0171] The fluidity test method is as follows: inject the stirred pure slurry into the truncated cone mold, lift the truncated cone original mold, and measure the maximum diameter of the slurry flowing freely on the glass plane. Truncated cone mold: 36mm upper diameter, 60mm lower diameter, 60mm height, smooth inner wall without joints, metal product; glass plate: 400mm×400mm×5mm; steel ruler: 300mm. Place the glass plate in a horizontal position, wipe the glass plate, truncated cone mold, stirrer and stirring pot with a wet cloth to make the surface wet without water stains. Place the truncated cone mold in the center of the glass plate and cover it with a wet cloth for use.

[0172] Quickly inject the mixed clean liquid into the truncated cone mold, scrape it flat with a scraper, lift the truncated cone mold in the vertical direction, start the stopwatch at the same time, and let the cement paste flow on the glass plate for 30 seconds. Use a ruler to measure the maximum diameters of the flowing part in two directions perpendicular to each other, and take the average value as the fluidity of the cement paste.

[0173] Fluid solidification strength, unit: kPa. The test method is: put the mixed fluidized soil into a rectangular test mold with a size of 40mm×40mm×160mm; the soil in the test mold is cured in a standard curing room, and after curing for a specified time, the compressive strength of the solidified soil at different time periods is tested using a press with an accuracy of 1N.

[0174] In a further embodiment, the following case is given.

[0175] Experiment on the effect of surfactant dosage on the fluidity of flowing silt sand: The raw materials of flowing silt sand mainly include: water, silt sand, machine-made sand, surfactant, curing agent, and newly produced desulfurization tower bottom ash. The dosage of curing agent in the mix ratio is constant at 6% of the total mass. The dosage of surfactant is adjusted to test the effect of different dosages of surfactant on fluidity.

[0176]

[0177] It can be seen from the above table that the more surfactant is added, the better the fluidity of silt sand. When the surfactant dosage X is less than 3%, the fluidity of silt sand is poor from the three parameters of yield stress, plastic viscosity and fluidity; when the surfactant dosage is 6% ≥ X ≥ 3%, the silt sand already has very good fluidity and can achieve the effect of self-compacting filling; when the surfactant X is greater than 6%, because the fluidity of silt sand has reached a very good state, that is, it is almost at the limit of this fluid material, the fluidity change is relatively small. Considering the economy and flow performance, the maximum dosage of surfactant is controlled within 6%. The specific trend of change is as follows Figure 5 As shown, the horizontal axis is the surfactant dosage, and the vertical axis is the yield stress and plastic viscosity.

[0178] Experiment on the effect of curing agent dosage on the strength of fluidized silt sand: the surfactant dosage in the mix ratio was kept constant at 4% of the total mass, the curing agent dosage was adjusted, and the change of curing strength over time at different curing agent dosages was tested.

[0179]

[0180] It can be seen from the above table that when the curing agent dosage Y is less than 5%, the compressive strength within 24 hours is low;

[0181] When the curing agent dosage is 10% ≥ Y ≥ 5%, the early strength of the fluidized silt sand can be achieved by adjusting the curing agent dosage. The higher the curing agent dosage, the higher the compressive strength. When the curing agent Y> 10%, the fluidized soil will lose its fluidity within 1 hour and cannot be transported by filling or pipelines.

[0182] Experiment on the influence of the specific surface area of ​​the mixture of "mineral powder, fly ash, and steel slag" in the curing agent on the strength of the solidified body: "Mineral powder, fly ash, and steel slag" in the curing agent are important components of the curing agent, and their specific surface area is directly related to the solidification and hardening speed and the strength of the solidified body. The surfactant content in the mix ratio is constant at 4% of the total mass, and the curing agent content is constant at 6%. The curing strength changes over time when the different specific surface areas of "mineral powder, fly ash, and steel slag" in the curing agent are tested.

[0183]

[0184] The test results show that the larger the specific surface area, the faster the solidification and hardening speed and the higher the early strength.

[0185] In short, in order to solve the current engineering problems of slow construction speed, difficult operation and low engineering quality assurance rate in the backfilling of small parts of space, the silt sand can be fluidized and quickly solidified and hardened through measures such as raw material optimization, specific mix ratio and specific construction procedures. The fluidity of silt sand can be fully utilized to fill the foundation pit in small parts of space, and the construction method of backfilling the foundation pit in small parts of space by manual compaction can be changed, so as to achieve a significant improvement in the construction speed, safety and quality of the foundation pit backfilling.

[0186] In this application, in order to meet the requirements of construction, the silt soil needs to have good fluidity after mixing, so as to facilitate construction, and after the construction is completed, it can be cured as soon as possible to meet the engineering requirements. However, this control is relatively complicated. Due to certain contradictions, this problem has not been solved in the prior art. In the prior art, if the fluidity is good, the curing speed will be relatively slow, and vice versa. Therefore, the prior art cannot simultaneously obtain good fluidity and meet the requirements of rapid curing.

[0187] In the present invention, by selecting and proportioning the surfactant and curing agent components and designing the specific surface area of ​​the curing agent, it is achieved that very good fluidity can be maintained for a period of time after stirring, so that the construction efficiency is higher, and after the construction is completed, the curing speed is very fast, thereby being able to meet the requirements of the project and improve the quality of the project.

[0188] The preferred embodiments of the present invention are described in detail above; however, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, various equivalent transformations can be made to the technical solutions of the present invention, and these equivalent transformations all belong to the protection scope of the present invention.

Claims

1. A composition capable of rapidly fluidizing and solidifying silt sand, characterized in that: In parts by mass, including: 3-6 parts of surfactant, 5-10 parts of curing agent, 5-10 parts of desulfurization tower bottom ash; The specific surface area of ​​the curing agent is ≥500m 2 / kg or more; The surfactant comprises the following components in parts by weight: 10-20 parts of acetone, 20-25 parts of sodium sulfite, 8-12 parts of sodium bisulfite, 5-10 parts of sodium pyrosulfite, 5-10 parts of water, 20-30 parts of 37% industrial formaldehyde, 10-15 parts of sodium lignin sulfonate, and sodium hydroxide capable of adjusting the composition to a predetermined pH; The curing agent comprises the following components in parts by weight: 30-40 parts of mineral powder, 25-35 parts of fly ash, 10-20 parts of steel slag, 10-15 parts of calcium oxide, and 10-15 parts of sodium sulfate.

2. The composition for rapid fluidization and solidification of silt sand according to claim 1, characterized in that: The surfactant comprises the following components in parts by mass: 10-15 parts of acetone, 22-25 parts of sodium sulfite, 10-12 parts of sodium bisulfite, 5-7 parts of sodium pyrosulfite, 5-8 parts of water, 23-28 parts of 37% industrial formaldehyde, 12-14 parts of sodium lignin sulfonate, and sodium hydroxide capable of adjusting the composition to a predetermined pH.

3. The composition for rapid fluidization and solidification of silt sand according to claim 1, characterized in that: The surfactant is prepared by the following method: Add sodium sulfite, sodium bisulfite, sodium metabisulfite, acetone and water into the reaction kettle, raise the temperature to 50℃~65℃ in 15~45min, and keep the temperature constant for 0.5~1.5h; Cool down to below 60℃, add sodium lignin sulfonate and remaining formaldehyde into the reactor, continue to react for 1-2h, adjust the pH value of the solution to 10-12 with sodium hydroxide, raise the temperature to 80-95℃, continue to react for 2-3h, and complete the reaction; After the reaction is completed, the mixture is allowed to stand and cool to room temperature to obtain a surfactant suitable for silt sand.

4. The composition for rapid fluidization and solidification of silt sand according to claim 1, characterized in that: The sum of the three materials of mineral powder, fly ash and steel slag in the curing agent must account for less than 80% of the total mass of the curing agent, and the surface area of ​​the mixture of the three substances must not exceed 700m 2 / kg or more.

5. The composition for rapid fluidization and solidification of silt sand according to claim 1, characterized in that: Calcium oxide and sodium sulfate account for more than 20% of the total mass of the mixture.

6. A method for fluidizing and rapidly solidifying silt soil, which is achieved by using the composition according to any one of claims 1 to 5, and comprises the following steps: Step S1, preparing raw materials according to a predetermined ratio, wherein the raw materials include the following components in parts by weight: 30-40 parts of water, 40-50 parts of silt soil, 5-10 parts of sand, 3-6 parts of surfactant, 5-10 parts of curing agent, and 5-10 parts of desulfurization tower bottom ash; Step S2, uniformly mixing the above-mentioned water and surfactant in parts by mass to obtain a mixed solution; Step S3, putting the above-mentioned silt sand in the mixer, stirring for 15 to 45 seconds, adding the mixed solution and sand in step 2 into the mixer, stirring for another 2 to 3 minutes, to obtain a slurry-like fluidized silt sand; Step S4: Add the curing agent in the above mass fraction into a mixer and stir for 2 to 3 minutes to obtain a fluid and curable silt sand slurry.

7. The method according to claim 6, characterized in that The raw materials include the following components in parts by weight: 30-35 parts of water, 40-45 parts of soil, 5-7 parts of sand, 3-5 parts of surfactant, 6 parts of curing agent, and 8 parts of desulfurization tower bottom ash.

8. The method according to claim 6, characterized in that The sand is machine-made sand or river sand, and the particle size is 1.25 mm to 5.0 mm.

9. The method according to claim 6, wherein: The mixer is a disc vertical shaft mixer with a power of not less than 30 kW and a rotation speed of 60 r / min to 90 r / min.

Citation Information

Patent Citations

  • Backfill earth construction method by using premixed flow state solidified earth

    CN107816047A

  • Two-component quick-hardening early-strength liquid soil stabilizer and application thereof

    CN112159150A